2017
DOI: 10.1177/1046878117691076
|View full text |Cite
|
Sign up to set email alerts
|

Oasistan

Abstract: Aim. Although cultural dimensions theory is a topical strand of quantitative cultural research, few intercultural simulation games use it. We present the design and review of the application of OASISTAN, an intercultural roleplaying simulation game that is specifically based on cultural dimensions theory. Results. The game has a no-tech role-play design and revolves around the geopolitically complex region of the Caspian Sea, specifically the fictional country of 'Oasistan'. The game consists of students formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In addition, uncovering the feelings and messages associated with role play extend well beyond the game and can have other practical purposes. de Jong and Warmelink’s (2017) research showed that experiencing cultural differences can be challenging and sometimes uncomfortable for some learners. They used game design and role play to assist learners with understanding cultural differences as learners took on the culture of a person other than their own.…”
mentioning
confidence: 99%
“…In addition, uncovering the feelings and messages associated with role play extend well beyond the game and can have other practical purposes. de Jong and Warmelink’s (2017) research showed that experiencing cultural differences can be challenging and sometimes uncomfortable for some learners. They used game design and role play to assist learners with understanding cultural differences as learners took on the culture of a person other than their own.…”
mentioning
confidence: 99%